Estrogen and Aging Affect Synaptic Distribution of Phosphorylated LIM Kinase (LIMK) in CA1 Region of Female Rat Hippocampus - Yildirim, Murat (2008)
17β-Estradiol (E) increases axospinous synapse density in the hippocampal CA1 region of young female rats, but not in aged rats. This may be linked to age-related alterations in signaling pathways activated by synaptic estrogen receptor α (ER-α) that potentially regulate spine formation, such as LIM-Kinase (LIMK), an actin depolymerizing factor/cofilin kinase. We hypothesized that, as with ER-α, phospho-LIMK (pLIMK) may be less abundant or responsive to E in CA1 synapses of aged female rats. To address this, cellular and subcellular distribution of pLIMK-immunoreactivity (pLIMK-IR) in CA1 was analyzed by light and electron microscopy in young and aged female rats that were ovariectomized and treated with either vehicle or E. pLIMK-IR was found primarily in perikarya within the pyramidal cell layer and dendritic shafts and spines in stratum radiatum (SR). While pLIMK-IR was occasionally present in terminals, post-embedding quantitative analysis of SR showed that pLIMK had a predominant post-synaptic localization and was preferentially localized within the postsynaptic density (PSD). The percentage of pLIMK-labeled synapses increased (30%) with E treatment (p<0.02) in young animals, and decreased (43%) with age (p<0.002) regardless of treatment. The pattern of distribution of pLIMK-IR within dendritic spines and synapses was unaffected by age or E treatment, with the exception of an E-induced increase in the non-synaptic core of spines in young females. These data suggest that age-related synaptic alterations similar to those seen with ER-α occur with signaling molecules such as pLIMK, and support the hypothesis that age-related failure of E treatment to increase synapse number in CA1 may be due to changes in the molecular profile of axospinous synapses with respect to signaling pathways linked to formation of additional spines and synapses in response to E.